Uma análise sobre a exposição de dados em redes sociais dos alunos da área de informática - Lira, Elsianne Serudo Marinho (Brasil, 2020)
The internet has become the biggest social communication tool, since Social Networks have made it possible to socialize people from remote places. But with the promotion of communication, there was also exposure, which created a vulnerability in the medium. In this context, this work aims to demonstrate the level of vulnerability through the Social Engineering of Computer Students based on the exposure of data on social networks. Finally, through a Bibliographic Research and Application of the Spear phishing technique, the study shows that even with all the evolution of information security systems, the human factor will always be the most vulnerable element in security management.